A large observational cohort study of rheumatoid arthritis, IORRA: Providing context for today's treatment options. Issue 1 (2nd January 2020) - Yamanaka, Hisashi; Tanaka, Eiichi; Nakajima, Ayako; Furuya, Takefumi; Ikari, Katsunori; Taniguchi, Atsuo; Inoue, Eisuke; Harigai, Masayoshi
Abstract: Real-world evidence, based on real-world data from routine clinical treatment, is becoming increasingly important for providing high-quality medical care. Large-scale cohort studies can provide useful access to some of this real-world evidence, as shown by the IORRA (Institute of Rheumatology, Rheumatoid Arthritis) cohort in Japan. This large cohort study of patients with rheumatoid arthritis (RA) has been surveying enrolled participants since its inception in 2000. In the last 19 years, it has served as a database for a wide range of research in areas including transitions in medical care at the clinical level, changes in therapeutic drugs, approaches to comorbidities, developments in pharmacoeconomics, and the effects of genomic information on treatment options. This research has resulted in the publication of 133 articles in English to date. IORRA monitors changes in the management of RA, and has quantified over time the daily experience of clinicians who provide routine medical care. Such observational databases, which reflect the reality of daily clinical practice, will become increasingly important and may provide a model for similar research in other disease areas.